Bioelectrical spectroscopy impedance phase angle is not associated with nutritional status in a stable cohort of paediatric inflammatory bowel disease patients. (August 2021) - Ashton, James J.; Marino, Luise V.; Johnson, Mark J.; Newell, Colin; Price, Gabrielle; Dewar, Helen; Brampton, Rachel; Ennis, Sarah; Griffiths, Mark; Coelho, Tracy; Batra, Akshay; Afzal, Nadeem; et al.
Summary: Background & aims: Nutritional assessment in paediatric inflammatory bowel disease (IBD) is key to supporting growth whilst minimising adiposity. Bedside assessment using bioelectrical impedance spectroscopy (BIS) has previous identified patients with declining cellular and nutritional health. We aimed to assess BIS measures in stable paediatric IBD patient. Methods: Stable IBD patients were recruited at routine hospital visits. All patients underwent BIS, anthropometry and disease activity assessment. Multivariable regression and receiver operator curve (ROC) analyses were undertaken to assess the utility of BIS phase angle 50 KHz (PA-50) and 200/5 KHz impedance ratio (IR) in nutritional assessment. Results: There were 140 study visits from 97 patients, mean age 14.49 years, 62.9% Crohn's disease. Mean BMI Z-score (BMIZ) was 0.31 (range −2.97 to 3.99), 33% of patients were overweight (BMIZ>1) and 13.8% of patients were underweight (BMIZ < −1). Crohn's disease patients had a lower mean BMIZ score 0.14, compared to ulcerative colitis, 0.68, p = 0.007. There was no relationship between PA-50 and BMIZ or disease activity. IR was not related to disease activity but was negatively related to BMIZ in a multivariable regression, accounting for age, sex and disease subtype (beta −0.331, p = 0.001). ROC analyses did not identify a clinically useful cut off for either PA-50 or IR to identify patients with active disease, biologic use or BMIZ>1 or < -1. Conclusion: BIS appears to have limited added value in nutritional assessment of stable paediatric IBD patients. Nearly 1/3 patients were overweight and personalised approach to supplementation is vital to avoid overnutrition.